F-18 FDG PET-derived imaging biomarkers of airway inflammation and their clinical associations in patients with non-small cell lung cancer - Ju Hyun Oh; Su Jin Lee; Yong-Jin Park (BMC Cancer)
Abstract Background Airway inflammation is believed to play a crucial role in the development and progression of non-small cell lung cancer (NSCLC). However, no study has yet employed quantified imaging biomarkers to assess airway inflammation in patients with NSCLC. This study aimed to validate the hypothesis that airway inflammation is more pronounced in a large cohort of patients with NSCLC compared to controls, using airway imaging biomarkers derived from fluorine-18-fluorodeoxyglucose (F-18 FDG) positron emission tomography (PET), as well as to explore their associations with clinical parameters. Methods We retrospectively enrolled 618 patients with NSCLC and 441 controls who underwent F-18 FDG PET/computed tomography (CT). The F-18 FDG PET/CT images were subjected to airway segmentation to determine the airway maximum standardized uptake value (SUVmax) and total lesion glycolysis (TLG). We compared the airway PET parameters between patients with NSCLC and controls. Additionally, we investigated the associations between airway PET parameters and tumor SUVmax, stages, smoking pack-years, histological subtypes, systemic inflammation, and lung function in patients with NSCLC. Results The median airway SUVmax (P < 0.0001) and TLG (P < 0.0001) were significantly higher in patients with NSCLC than in controls. The median airway SUVmax (P = 0.0098) and TLG (P < 0.0001) were significantly higher in patients with squamous cell carcinoma than in those with adenocarcinoma. Airway SUVmax and TLG showed weak positive correlations with tumor SUVmax, stages, white blood cell count, and neutrophil-to-lymphocyte ratio, but weak to moderate negative correlations with lung function parameters. Airway TLG showed a moderate positive correlation with smoking pack-years. Conclusions F-18 FDG PET-derived airway imaging biomarkers were higher in patients with NSCLC than in controls. Additionally, these biomarkers were associated with tumor SUVmax, stages, histological subtypes, serologic inflammatory markers, lung function, and smoking, suggesting their potential to provide insights into the development and severity of NSCLC.